The Difference Participant of Wirid Remaja in Wirid Remaja Activities Using and Not Using Powerpoint Media in Kelurahan Air Tawar Timur - Putri Nopita Sari; Solfema Solfema; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research describes the effectiveness of using powerpoint media on adolescent learning in the mosque Air Tawar Timur. The population in this research is 40sampels, with a total sample of 20 people using a cluster sampling technique. The main instrument of this research is observation. Based on the research, result of uji hipotesis is thitung> ttable(2,09 <9,30>2,86). The difference in control class increase to experiment class is significant. So this activity can be effective when using powerpoint media.Keywords: Learning Media, Participation